1970
DOI: 10.1063/1.1658474
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Limited Phase Transformations: A Comparison and Critical Evaluation of the Mathematical Approximations

Abstract: Mathematical analyses previously made for diffusion-limited growth and dissolution of spherical and planar precipitates have been reviewed. The analyses include the invariant-field (Laplace), the invariantsize (stationary interface) and the linear-gradient approximations, and where possible, exact solutions of the differential time-dependent diffusion equation and of the independent flux balance. The kinetic parameters are calculated and the different solutions compared. For virtually all cases of practical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
204
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(224 citation statements)
references
References 6 publications
6
204
0
3
Order By: Relevance
“…Glicksmann evaluated the movingboundary problem of 3D precipitate growth in relation to the static-boundary case [22], and found that for small supersaturations the difference is negligible. A similar analysis has been done by Aaron and coworkers in the context of diffusional phase transformations [23].…”
Section: Discussionmentioning
confidence: 75%
“…Glicksmann evaluated the movingboundary problem of 3D precipitate growth in relation to the static-boundary case [22], and found that for small supersaturations the difference is negligible. A similar analysis has been done by Aaron and coworkers in the context of diffusional phase transformations [23].…”
Section: Discussionmentioning
confidence: 75%
“…k Þ with the exact analytical solution of the diffusion problem in a semiinfinite matrix for a binary alloy [8,25]:…”
Section: Growth/coarseningmentioning
confidence: 99%
“…In the model the growth and coarsening of the existing groups of precipitates during each time step is evaluated by [39,40,41]:…”
Section: Growth/coarsening Of S Phasementioning
confidence: 99%